2012
DOI: 10.3329/jbau.v10i1.12035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cowdung and potassium on growth and yield of Kohlrabi

Abstract: An experiment was carried out at the Horticulture Farm of the Bangladesh Agricultural University, Mymensingh during the period from November 2010 to January 2011 to study the effects of cowdung and potassium on growth and yield of Kohlrabi. The experiment consisted of three levels of cowdung (0, 20 and 40 t/ha) and four levels of potassium (0, 20, 50, 80 kg /ha). The experiment was laid out in randomized complete block design with three replications. All the parameters were significantly influenced by applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 4 publications
5
9
0
Order By: Relevance
“…The results indicated that application of organic fertilizers and inorganic fertilizers combined showed improved growth and the maximum plant spread. These findings are in agreement with the reports where vermicompost or poultry manure along with inorganic fertilizer application yielded high plant spread [27][28][29]. Level of significance ** ** ** ** NS ** ** ** S 1 = 60 cm × 40 cm; T 1 = Vermicompost; S 2 = 60 cm × 50 cm; T 2 = Biogen; S 3 = 60 cm × 60 cm; T 3 = IPNS ( 2 /3 organic + 1 /3 inorganic) and T 4 = Inorganic; ** = Significant at 1% level of probability.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results indicated that application of organic fertilizers and inorganic fertilizers combined showed improved growth and the maximum plant spread. These findings are in agreement with the reports where vermicompost or poultry manure along with inorganic fertilizer application yielded high plant spread [27][28][29]. Level of significance ** ** ** ** NS ** ** ** S 1 = 60 cm × 40 cm; T 1 = Vermicompost; S 2 = 60 cm × 50 cm; T 2 = Biogen; S 3 = 60 cm × 60 cm; T 3 = IPNS ( 2 /3 organic + 1 /3 inorganic) and T 4 = Inorganic; ** = Significant at 1% level of probability.…”
Section: Resultssupporting
confidence: 93%
“…Results showed that the wider spacing was superior in yield attributes. Similar findings in the plant height of cabbage were obtained by various researchers [25,26] and IPNS or the application of mixed fertilizers influenced the plant height [27,28]. The wider spacing did not produce highest yield as number of plants reduced by the unit area.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…gongylodes), a member of the cole crops, which belongs to the family Cruciferae is of north-European origin. 1 It is also known as Knolkhol German turnip, cabbage turnip, Navalkol, GunthGobhi, and Ganthgobhi 2 and Olkapi. 1 The bulb like swollen edible portion is stem known as knob, which arises from thickening of stem tissues above the cotyledon.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is also known as Knolkhol German turnip, cabbage turnip, Navalkol, GunthGobhi, and Ganthgobhi 2 and Olkapi. 1 The bulb like swollen edible portion is stem known as knob, which arises from thickening of stem tissues above the cotyledon. 2 This knob is harvested for human consumption as raw or cooked vegetable.…”
Section: Introductionmentioning
confidence: 99%